Residential Noise Exposure and Health: Evidence from Aviation Noise and Birth Outcomes - Laura M. Argys; Susan L. Averett; Muzhe Yang (Institute of Labor Economics (IZA), 2019)
Exploiting recent concentration of flight patterns under a new Federal Aviation Administration policy (called NextGen), we examine the impact of exposure to excessive noise levels on birth outcomes. Using birth records that include mothers' home addresses to measure airport proximity, we find the risk of low birth weight babies increases by 17 percent among mothers living near the airport in the direction of the runway. We utilize exogenous variation in noise exposure triggered by NextGen, which unintentionally increased noise in communities affected by the new flight patterns. Our finding informs policy-makers regarding the trade-off between flight optimization and human health.
Keywords: I10; I18; Q53; Q58; R11; 330; noise; airport runway; low birth weight; NextGen